2015
DOI: 10.1093/femsle/fnv092
|View full text |Cite
|
Sign up to set email alerts
|

Methanogen communities in stools of humans of different age and health status and co-occurrence with bacteria

Abstract: Hydrogenotrophic methanogens live in a synthrophic relationship with the human gut microbiota as the terminal part of the anaerobic food chain. Methanobrevibacter smithii of the Methanobacteriales is the prevailing archaeal species. Recently, methylotrophic archaea of the novel order Methanomassiliicoccales were isolated from human stools. Few data exist on the prevalence, abundance, persistence and ecology of these methanogens in humans. This study investigated methanogen communities in 26 healthy and obese c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 43 publications
3
38
1
Order By: Relevance
“…Differences between microbial communities (ß-diversity) were measured by unweighted and weighted UniFrac analysis (Lozupone et al, 2007) using QIIME. Principal coordinates analysis (PCoA) plots/biplots were generated by EMPeror based on weighted UniFrac analysis and relative abundances of the most common microbial taxa (V azquez-Baeza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Differences between microbial communities (ß-diversity) were measured by unweighted and weighted UniFrac analysis (Lozupone et al, 2007) using QIIME. Principal coordinates analysis (PCoA) plots/biplots were generated by EMPeror based on weighted UniFrac analysis and relative abundances of the most common microbial taxa (V azquez-Baeza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing depth was not significant (p-value = 0.73) and was subsequently removed. BMI and age were correlated with the Chistensenellaceae abundance (p-value = 0.0002 for the correlation with BMI and 0.02 for the correlation with age). As Methanobrevibacter smithii has been associated with age (23) and BMI (4, 43, 4548, 68, 69), we first added the interaction factors to the models: the interaction factors were not significant with BMI (p-values = 0.11 and 0.07, for both Methanobrevibacter and Methanobacteriaceae , respectively). However, the interactions with age were significant (p-values = 0.004 and 0.002, for both Methanobrevibacter and Methanobacteriaceae, respectively) and therefore, both variables were kept in the models.…”
Section: Appendixesmentioning
confidence: 99%
“…The most widespread and abundant of the gut methanogens, Methanobrevibacter smithii , produces CH 4 from H 2 and CO 2 , the products of bacterial fermentation of dietary fibers. Such cross-feeding likely explains why the relative abundances of M. smithii and fermenting bacteria are often positively correlated (21, 23, 24). Several studies have shown that in the laboratory, M. smithii can grow from the H 2 provided by Bacteroides thetaiotaomicron , a common gut commensal bacterium (2527).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Borrel, Brugère, O'Toole and colleagues have made advances in expanding the prevalence of methanogens to include lineages assigned to the newly described seventh order, Methanomassiliicoccales (Borrel et al, 2013;Borrel et al, 2014), which also includes the often referenced "rumen cluster C" from livestock surveys (Janssen and Kirs, 2008). A combination of both culture-based and genomic studies have characterized the narrow substrate range used by members of this order (methanol and/or methylated amines) and found that members of this order appear to be more prevalent in mature age persons (Borrel et al, 2014;Gaci et al, 2014;Vanderhaeghen et al, 2015). In addition to pectins being a source of methanol, other food components such as choline, lecithin, and L-carnitine can be transformed by bacterial fermentation into methylated amines.…”
Section: Methane Matters To the Health Of Humans Toomentioning
confidence: 99%